Investigating the introduction of economic land use developments to create rail contra-flow using a strategic model: a case study of Johannesburg - Ngobeni, Ntombifuthi (Department of Civil Engineering, 2020)
South Africa is still recovering from the effects of the apartheid government and spatial design that marginalises the demographic that resides at the edges and outskirts of cities. The country has come a long way from where it was, but still has a long way to go to eradicate the effects this fragmentation has had on access to socio economic opportunities. Diversifying land use and creating localised economic hubs may provide a helping hand in reducing the need to travel far distances to seek opportunity, and by extension create an attraction for surrounding communities. The dual role of nullifying past prejudice implemented through strategic spatial design while introducing the perspective of using the relationship between land use and transport to create rail contra flow and localised socio-economic hubs is one that can be achieved strategically. The modelling software that will help to demonstrate the model output of the research, which will be a simulation of contra-flow after the introduction of economic land use developments, is PTV VISUM.